Perpetuating Health Disparities of Minority Groups: The Role of U.S. Newspapers in the COVID-19 Pandemic - Xu, Zhan (Race and social problems, 2022)
During the COVID-19 pandemic, news media are expected to play a critical role in reducing health disparities. However, we know little about whether and how disparities in COVID-19 have been covered in national and local U.S. newspapers. This study examined whether minority health gained news attention and whether partisan bias affected related coverage in the early stages of the pandemic. Results indicate that minority groups have been underrepresented in COVID-19 news articles. Left-leaning newspapers were more likely to discuss minorities in COVID-19 news than least biased media. Left-leaning and right-leaning newspapers did not differ in the number of articles mentioning racial/ethnic minorities. COVID-19 news exceeded the average U.S. reading comprehension level and require some college education to understand but did not differ in readability levels among partisan newspapers. Left-leaning newspapers used significantly more medical terms and affiliated scientific facts to describe COVID-19 than right-leaning newspapers. Implications include avoiding potential failures in informing the public (especially the racial/ethnic minorities) essential scientific facts about disease prevention and increasing public trust in health news coverage.